A Taxonomy of Secondary School Athletic Team Names and Mascots in the United States. (2nd October 2018) - Zeitler, Ezra J.
Abstract : Athletic team names are a fascinating yet understudied topic in onomastics. Inspired by the work of Nuessel (1994 ) and Smith (1997) and framed by the extensive toponymy approach described by Tent (2015 ), this study proposes a taxonomy of team names and mascots used by high schools in the United States. A list of 20, 853 schools procured from the Clell Wade Coaches Directory catalyzed the study, and content analysis of school websites and social media accounts determined the mascots of ambiguous team names. The results include seven general categories: humans, fauna, flora, inanimate objects and phenomena, deities and spiritual beings, mythological creatures and beings, and schools not using team names. Most schools use an animal or human mascot, and prevailing themes among all names include a strong degree of convention in their selection, a high frequency of bellicosity in their character, and a small but notable observance of local distinctiveness in their presence.